Social Context in Mangalua’s Novel by Idris Pasaribu: A Literature Sociology Study - Meriah Kita Deliani; Rosliani Rosliani (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
This paper focuses on the world view of the author in the Mangalua’s novel by Idris Pasaribu and the author's world view of social reality as depicted in the Mangalua’s novel by Idris Pasaribu. This study used a qualitative descriptive method with a sociological literature approach. The data collection technique was carried out by document analysis, while the data analysis used descriptive qualitative methods. The results showed that this novel contains the social context in the novel which is depicted through the main character, social structure, marriage customs, and religion. The results of the analysis of social context with the approach of genetic structuralism in the novel, found that the author's world view is influenced by background, experience and insight, as well as social groups.